Thermogenic activity of growth hormone transgenic mice - Moura, A. S.A.M.T. [UNESP]; Spiers, D. E.; Lamberson, W. R. (My University, 1998)
The objective was to determine the effect of a mouse metallothionein/bovine growth hormone transgene on resting metabolic rate (RMR), cold-induced thermogenesis, and β-agonist stimulated nonshivering thermogenesis in mice. Non-transgenic littermates were used as controls. Open-circuit indirect, calorimetry was used to assess RMR and cold-induced thermogenesis in 64 mice. Air temperature in the chamber was set at 31°C for RMR and was decreased to 28, 25, 21, or 17°C to determine cold-induced thermogenesis. Response to the β-agonist isoproterenol was evaluated by monitoring changes in colonic temperature of 34 mice upon injection of the drug or saline. Despite the fact that RMR tended to be lower in transgenics than in nontransgenics, at 31°C transgenic mice were able to regulate colonic temperature at the same level as nontransgenics, but colonic temperature decreased in transgenics relative to nontransgenics as air temperature was reduced. For each degree decrease in air temperature between 31 and 17°C, nontransgenic mice increased heat production by 1.03 ± .10 watt/kg, whereas transgenic mice increased it by only .56 ± .08 watt/kg, indicating that the thermogenic response of transgenics to cold was inferior. The magnitude of the maximal increase in colonic temperature after isoproterenol injection was similar for both groups, but the response was slower in transgenics. We suggest that lean body mass and substrate availability for shivering thermogenesis are reduced in transgenics relative to total body weight, and that they allow colonic temperature to decrease to conserve energy.
Keywords: Beta-adrenergic agonist; Growth hormone; Metabolic rate; Mice; Thermoregulation; Transgenic